68‐4: Top‐emission OLED Kawara‐type Multidisplay with Auxiliary Electrode. Issue 1 (30th May 2018) - Nakamura, Daiki; Eguchi, Shingo; Sugisawa, Nozomu; Aoyama, Tomoya; Kato, Sho; Sasaki, Takeru; Kamada, Taisuke; Watanabe, Kazunori; Dobashi, Masayoshi; Misawa, Chieko; Nakada, Masataka; Yamazaki, Shunpei
Abstract : We have developed a top‐emission organic light‐emitting diode (OLED) Kawara‐type multidisplay with a novel auxiliary electrode. With this device, while the contact portion of the auxiliary electrode is developed in the display region, a high aperture ratio can be achieved. This technique can be utilized in any top‐emission OLED display.